Análise genômica comparativa de salmonella enterica sorovares heidelberg e typhimurium de origem avícola - Nascimento, Sebastião Rodrigo de Lima (2019)
Poultry farming is an activity of global importance. The United States of America and Brazil hold respectively the top two positions in world chicken production. The presence of multiresistant Salmonella isolates in chicken meat is a cause of worldwide concern for the public and animal health authorities, damaging the image and quality of this food. In the present study, 14 public genomes of Salmonella were selected from the NCBI platform: 8 Heidelberg (SH) and 6 Typhimurium (STM) serotypes originating from Brazil and the United States. These isolates were compared for the purpose of evaluating gene sets related to the antimicrobial resistance of these microorganisms. The results showed the presence of genes related to antimicrobial insensitivity, with high frequency for aminoglycosides (aac - Iaa) 100%, fosfomycin (fosA7) 50% (7 SH, 3 from Brazil and 4 from the USA), tetracycline tet(A) and sulfonamides (Sul2) 50% (3 SH from Brazil and 4 STM, 1 from Brazil and 3 from the USA) and 14.28% for beta-lactams (blaCMY-2)(2 SH from Brazil). Only 3 samples did not present a plasmid, whereas the rest of the isolates (11) had at least one plasmid. Among these, ColpVc, IncX1, IncA2, IncI1, IncFIB(S) and IncFII(S) were identified. Regarding the pathogenicity islands of Salmonella (SPI), SPI-1, SPI-2, SPI-3, SPI-4 and SPI-5 were found in all observed genomes, although some had low homology compared to the genome reference (SalmonellaSPI), with 4 SH and 1 STM from Brazil and 2 STM from the USA. Building the phylogenetic tree allowed to group the isolates into 3 clades that varied between the serotypes and countries from which they were isolated. SH cells found in Brazil showed more resistance genes when compared to those isolated in the United States and to STM isolates.